2018
DOI: 10.3390/rs11010036
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Multi-Sensor Data on the Detection of Margalefidinium polykrikoides in the South Sea of Korea

Abstract: Since 1995, Margalefidinium polykrikoides blooms have occurred frequently in the waters around the Korean peninsula. In the South Sea of Korea (SSK), large-scale M. polykrikoides blooms form offshore and are often transported to the coast, where they gradually accumulate. The objective of this study was to investigate the synergistic effect of multi-sensor data for identifying M. polykrikoides blooms in the SSK from July 2018 to August 2018. We found that the Spectral Shape values calculated from in situ spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Red tide patches vary significantly within a few meters and tend to move with ocean currents or winds. Shin et al [29] confirmed that red tide patches moved slightly northward between two satellite images obtained within 1 h. Thus, the difference between the sampling time used to estimate in situ cell abundances and HSI acquisition time can reduce verification accuracy. In particular, because M. polykrikoides is characterized by vertical migration, the difference in sampling time can be an important factor affecting performance.…”
Section: Performance Of New Red Tide Indexmentioning
confidence: 97%
See 3 more Smart Citations
“…Red tide patches vary significantly within a few meters and tend to move with ocean currents or winds. Shin et al [29] confirmed that red tide patches moved slightly northward between two satellite images obtained within 1 h. Thus, the difference between the sampling time used to estimate in situ cell abundances and HSI acquisition time can reduce verification accuracy. In particular, because M. polykrikoides is characterized by vertical migration, the difference in sampling time can be an important factor affecting performance.…”
Section: Performance Of New Red Tide Indexmentioning
confidence: 97%
“…Figure 1 shows in situ sampling locations used for the field survey and the flight lines of the hyperspectral images. Red, green, and blue dots indicate the sampling locations of the field surveys conducted on 7-8 August 2018 [29], 30-31 August 2019, and 25-26 September 2019, respectively. Black boxes show the flight routes used to acquire HSI at the time of the field surveys.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Shin et al [14], in their paper entitled "Synergistic Effect of Multi-Sensor Data on the Detection of Margalefidinium polykrikoides in the South Sea of Korea", performed a feasibility test to detect Margalefidinium polykrikoides blooms by identifying a possible synergistic effect of multi-sensor data. Their results showed that the detection performance of Margalefidinium polykrikoides blooms increased when multi-sensor data were used.…”
Section: Remote Sensing Technology and Its Applicationsmentioning
confidence: 99%